Vulnerability to unintentional injuries associated with land-use activities and search and rescue in Nunavut, Canada - Clark, Dylan G.; Ford, James D.; Pearce, Tristan; Berrang-Ford, Lea
Injury is the leading cause of death for Canadians aged 1 to 44, occurring disproportionately across regions and communities. In the Inuit territory of Nunavut, for instance, unintentional injury rates are over three times the Canadian average. In this paper, we develop a framework for assessing vulnerability to injury and use it to identify and characterize the determinants of injuries on the land in Nunavut. We specifically examine unintentional injuries on the land (outside of hamlets) because of the importance of land-based activities to Inuit culture, health, and well-being. Semi-structured interviews (n = 45) were conducted in three communities that have varying rates of search and rescue (SAR), complemented by an analysis of SAR case data for the territory. We found that risk of land-based injuries is affected by socioeconomic status, Inuit traditional knowledge, community organizations, and territorial and national policies. Notably, by moving beyond common conceptualizations of unintentional injury, we are able to better assess root causes of unintentional injury and outline paths for prevention. Unintentional injury; Canada; Arctic; Search and rescue; Inuit; Indigenous health; Vulnerability; Climate change;